Assessment of normal myelination in infants and young children using the T1w/T2w mapping technique - Filimonova, Elena; Amelina, Evgenia; Sazonova, Aleksandra; Zaitsev, Boris; Rzaev, Jamil (Frontiers in neuroscience, 2023)
White matter myelination is a crucial process of CNS maturation. The purpose of this study was to validate the T1w/T2w mapping technique for brain myelination assessment in infants and young children. Ninety-four patients (0-23 months of age) without structural abnormalities on brain MRI were evaluated by using the T1w/T2w mapping method. The T1w/T2w signal intensity ratio, which reflects white matter integrity and the degree of myelination, was calculated in various brain regions. We performed a Pearson correlation analysis, a LOESS regression analysis, and a 2 order polynomial regression analysis to describe the relationships between the regional metrics and the age of the patients (in months). T1w/T2w ratio values rapidly increased in the first 6-9 months of life and then slowed thereafter. The T1w/T2w mapping technique emphasized the contrast between myelinated and less myelinated structures in all age groups, which resulted in better visualization. There were strong positive correlations between the T1w/T2w ratio values from the majority of white matter ROIs and the subjects' age ( = 0.7-0.9, < 0.001). Within all of the analyzed regions, there were non-linear relationships between age and T1/T2 ratio values that varied by anatomical and functional location. Regions such as the splenium and the genu of the corpus callosum showed the highest R values, thus indicating less scattering of data and a better fit to the model. The T1w/T2w mapping technique may enhance our diagnostic ability to assess myelination patterns in the brains of infants and young children.